Human dirofilariosis in the 21st century: A scoping review of clinical cases reported in the literature. Issue 5 (10th July 2021) - Simón, Fernando; Diosdado, Alicia; Siles‐Lucas, Mar; Kartashev, Vladimir; González‐Miguel, Javier
Abstract: Human dirofilariosis is a clinical entity caused by infection with nematode species of the genus Dirofilaria . The traditional picture depicts the disease as a sporadic event associated with the presence of a single immature worm causing a nodular lesion. With the aim to reassess this paradigm, establishing a more accurate picture of the disease and homogenize criteria, a scoping review was conducted by searching, screening and analysing published clinical cases of human dirofilariosis worldwide during the 21st century. After extracting data from 305 publications containing 576 case reports, results showed that human dirofilariosis is currently caused by five Dirofilaria species (mainly D. repens ). Maturation was not uncommon, since 42.95% of the parasites recovered were described as mature worms, most of them females, 26.42% of which contained micofilariae in the uterus. Moreover, six microfilaremic cases have been described. The predominant clinical manifestation was the presence of a worm encapsulated within a nodule, but there is a considerable variety of accompanying symptoms depending on anatomical location and type of dirofilariosis. Parasites/nodules were found in 71 different anatomical locations, being the traditional nomenclature of human dirofilariosis unable to properly cover this complex situation. Delay in seeking medical assistance (patient perception) and the frequency of wrong clinical suspicions (doctor knowledge), strongly influenced clinical management. The initial suspicion in cases of subcutaneous and pulmonary dirofilariosis is predominantly a tumour, while in the ocular dirofilariosis a parasite (but not directly Dirofilaria ) is mostly suspected. Surgery is usually applied, regardless of the use of non‐invasive techniques during preoperative management and although its use is still limited, molecular approach is the most accurate technique to establish a species‐level diagnosis. Accurate epidemiological, parasitological and clinical information while handling and reporting human clinical cases is a need for physicians and researchers to improve and standardize the clinical management of human dirofilariosis.